Bike sharing - Key findings and recommendations. [SPICYCLES-Sustainable Planning & Innovation for Bicycles]. - (:unkn) unknown (My University, 2008)
Der Bericht fasst die Aktivitäten des Projekts "SPICYCLES-Sustainable Planning & Innovation of Bicycles" im Zeitraum von 2006-2008 zusammen. Er beinhaltet Informationen über den aktuellen Stand der Fahrradinfrastruktur in Bezug auf Bike Sharing Systeme in den am Projekt beteiligten Städten Berlin, Ploiesti, Barcelona, Rom, Göteborg und Bukarest. Auf der Basis dieser Informationen und Erfahrungen mit anderen Projekten werden Empfehlungen entwickelt.

This report summarises the activities for bike sharing within the project SPICYCLES (Sustainable Planning & Innovation for Bicycles). It includes information about the state-of-the-art of bike sharing and infrastructure in the participating cities as well as the achieved status. Furthermore it will reflect the way of development. Upon the basis of the experiences made in the cities and especially other experiences made since bike sharing is booming, key findings and recommendations are developed. The project SPICYCLES intended to demonstrate that the modal share of cycling can be increased in European cities with different geographical, climatic and cultural conditions. The experience with different types of means and measures will be disseminated to a wide audience in European cities. Within SPICYCLES, four technical work packages, covering four different subjects concerning cycling policy, were defined. This document will focus on bike sharing systems.
Keywords: Individualverkehr; Fahrradverkehr; Bike sharing; Handlungsempfehlung; Fahrradbenutzung; Fahrradinfrastruktur; öffentliches Fahrradverleihsystem; Projekt